2020
DOI: 10.5863/1551-6776-25.6.500
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Causes of Infusion Alarms in a Neonatal and Pediatric Intensive Care Unit: A Prospective Pilot Study

Abstract: OBJECTIVES To evaluate the incidence and causes of infusion alarms in a NICU/PICU setting. METHODS We conducted a 90-day prospective analysis of event logs downloaded daily from infusion pumps (syringe and volumetric pumps). The details about conditions surrounding alarm events were described daily by bedside nurses on a standardized form. The occlusion pressure alarm was set at 300 mm Hg on each device. RESULTS Forty-one pediatric patients including 12 neonates, mean weight 11.0 ± 11.3 kg (minimum–maximum, 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…There is no known evidence of direct patient harm from a change in absorbance of active ingredients or adjuvants. However, particles or turbidity can have serious adverse drug reactions in children and particularly in neonates [1][2][3] and therefore concurrent administration should be avoided. Furthermore, in clinical settings not only incompatibilities but also the knowledge of compatibilities is important for a safe infusion therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no known evidence of direct patient harm from a change in absorbance of active ingredients or adjuvants. However, particles or turbidity can have serious adverse drug reactions in children and particularly in neonates [1][2][3] and therefore concurrent administration should be avoided. Furthermore, in clinical settings not only incompatibilities but also the knowledge of compatibilities is important for a safe infusion therapy.…”
Section: Discussionmentioning
confidence: 99%
“…1 This can cause complications such as catheter occlusion, blood-vessel irritation, or embolism. 2,3 Chemical reactions can lead to a degradation of the drugs and are considered as significant when more than 10% degradation occurs. 1 As a result, a reduced effectiveness can be seen in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that due to line occlusions, drug incompatibilities, and patient factors, alarms from infusion pumps were frequent in the NICU/pediatric ICU. 53 This also implies that more training or special coordination is required of nursing staff in those units with respect to infusion administration.…”
Section: Discussionmentioning
confidence: 99%
“…Within critical care, and particularly in pediatric and neonatal critical care, evidence is beginning to emerge that incompatibility between medications can cause the precipitation of medications in the venous access device [ 1 ], which may result in intravenous access failure or partial occlusion of peripheral access devices and central lines. A recent study [ 2 ] showed that venous access occlusion alarms are responsible for 55% of all intravenous infusion pump alarms in neonatal intensive care units and that noninfusion of critical short–half-life infusions (due to such occlusions) has the potential to cause severe cardiovascular instability in critical care patients receiving vasoactive medications.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of limited access and multiple infusions running into a single venous access device is common in critical care, particularly in pediatric and neonatal critical care settings. Fonzo-Christe et al [ 1 ] suggested that the filtration of medications might be one method of reducing the risk of precipitation during multiple concurrent infusions; however, the questions—for which medications? and how can we ensure that nursing staff are aware of and able to comply with such requirements?—should be asked.…”
Section: Introductionmentioning
confidence: 99%